Determinants of Poverty in Indonesia (Sociología y tecnociencia, 2021)
In Indonesia, the poverty profile is relatively robust and has become a national problem, especially the inequality gap between rich and poor is widening. In this wake, the main purpose of this study was to analyze the factors that have influenced the poverty in Indonesia since 2013 until 2019.  The poverty was measured based on the basic needs approach. The secondary data, retrieved from Central Bureau of Statistics and the Ministry of Finance, Republic of Indonesia, were used. The aggregated percentage of poverty from 34 provinces in Indonesia was employed as dependent variable. Meanwhile, the independent variables were the human development index, social protection, program, and unemployment. Multiple linear regression models were applied to test the hypotheses. This research revealed that human development index, and social protection program had significant but negative impact on poverty. In contrast, the unemployment had a positive but less significant impact on the poverty. Thus, the government must improve HDI, promote social protection, and apply innovative employment programs to alleviate poverty.
Keywords: Poverty; Human Development Index; Social protection, and Unemployment program; Indonesia.